Sex, sexuality, law and (in)justice - Fradella, Henry F.; Sumner, Jennifer Mortensen; Sumner, Jennifer Macy (Routledge, Taylor & Francis Group, 2016)
An overview of sex, gender, and sexuality / Patrick Englert and Elizabeth G. Dinkins -- Historical perspective / Ann Marie Nicolosi -- Sex and the Fourteenth amendment, Part I : due process of law / Stephen S. Owen and Tod W. Burke -- Sex and the Fourteenth amendment, Part II : equal protection of the law / Stephen S. Owen and Tod W. Burke -- Rape and related offenses / Henry F. Fradella and Chantal Fahmy -- The criminal regulation of sex : the limits of morality and consent / Henry F. Fradella and Kenneth Grundy -- The regulation of sex work and sex workers / Elisabeth Jandro -- Obscenity and pornography / Weston Morrow, Chantal Fahmy, and Henry F. Fradella -- Marriage, sexuality, and gender / Henry F. Fradella, Megan Parry and Lauren E. Fradella -- Rare acts, sympathetic victims, and the emergence of laws to -- Regulate sex offenders / David Patrick Connor -- Sex in jails and prisons / James E. Robertson -- Sex offenders and their treatment / Thomas Nolan and Mary Maguire -- Sex, gender, sexuality, and victimology / Jayn von Delden